(untitled) (Al-Academy, 2017)
Me researcher in this research study and discover the symbolic indications in the work of the Iraqi sculptor Morteza Haddad, has corrupted search of four chapters first chapter contains research problem and its significance and objectives of the research, which was to detect signs symbolism in works of contemporary Iraqi sculptor Morteza Haddad and terminology, which included significant the GTA and idiomatically and Velsfatta and conduct, It also included the symbol for GTA and idiomatically and Velsfatta and hold, while the second chapter includes three sections are straight, semantics and icon, a brief on Iraqi contemporary sculpture, About the lives of contemporary Iraqi sculptor Then choose the terms of the research sample, The analysis of the business, which contained five acts chosen by the researcher deliberate way that serves the orientations of the search, and then the fourth quarter, which included the conclusions summarized,First, the sculpture of the Iraqi general with the same semantic in nature and Ashari special and symbolic, carries deep into its components spirit of originality dissolved heritage of cultural and intellectual heritage, the nation’s art refined and rooted identity and Mughal-footed, we’re seeing the real pure form antiquity of the gene inherited from generation to generation, which has the honor to carry it all iconic Iraqis, Creativity, who carried his banner own identity pioneers realized the survival of the environment in which they were born of them,And being loaded and full of references and symbols, it must be clearly reflected with most of the technical, cultural and humanitarian outcomes related thereto, whether scientific or ideological or intellectual or historical ... etc, all the pictures, what was such a mythical or epic or narrative or my status ... etc, Kgaya inherited and transmitted lessons and folk traditions, including, in particular, works of art, and accurately Description sculpture, in terms of he finest record that moved us most of the joints of this knowledge through the ages.Second, semantic effect and hermeneutical, in the ancient and the modern Iraqi sculptural works, part of a coherent and parcel of the rest of the components work. Most business sculptural Mesopotamian, it has to carry between Jnabadtha a lot of signs and symbols that translate eternal relationship between art and the environment and the artist as an indication aware.Third: the alphabet of our language multiple meanings and different dialects and a variety of names and different interpretations and creations Mbdeina reflect these scripts in various ways, and that carried the same implications indicative and symbolic.Fourth, the most important features artwork plastic sculptured Iraqi ..ho contain different connotations, increase the impact of the Iraqi receiver gourmet.Fifth: knowledge of academic sculptor Morteza mourning Mosusath intellectual capacity, enabled him to employ the code to work, perhaps employing the work of the code sometimes, and this privacy make this business a distinct characteristic different from what distinguishes other Iraqis innovators in this field. The recommendations and suggestions.